THE EFFECT OF BENEFITS, BARRIERS, AND SELF-EFFICACY ON PUBLIC HEALTH PROMOTION BEHAVIOR DURING THE COVID-19 PANDEMIC - Dheni Koerniawan (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Pandemic of Covid-19 situation made people to adapt wiht new normal habitually. Health promotion behavior may determine by perceived benefit, barrier, and self-efficacy. Objectives: This research aimed to know the effect of perceived benefit, barrier, and self-efficacy to health promotion behavior in Palembang during pandemic Covid-19. Methods: This study done with cross-sectional design to 183 respondents who lived in Palembang taken by randomized with online questionnaire. The instrument of this study conducted from Pender’s HPM model developed by author. Study result analyzed by SEM-PLS approach to test direct and indirect effects. Results: The results showed that there was not significant effect of self-efficacy to barrier (β= -0.137; p= 0.067) and health promotion behavior (β= -0.026; p= 0.711), but the findings also showed significant effect of self-efficacy to benefit (β= 0.212; p= 0.017), benefit to barrier (β= -0.152; p= 0.046), barrier to health promotion behavior (β= -0.141; p= 0.039), and benefit to health promotion behavior (β= 0.331; p< 0.001). Otherwise, there was also found significant indirect effect of self-efficacy to health promotion behavior by benefit as mediator (β= 0.07; p= 0.026). Overall model give 14.2% to HBP. Conclusion: Perceived benefits and perceived barriers are significant predictors of individual health promotion behavior. Meanwhile, self-efficacy does not have a significant effect. In addition, self-efficacy has a significant influence on perceived benefits and perceived benefits on perceived barriers. Self-efficacy also has an indirect influence on health promotion behavior through perceived benefits as mediators